The Effect of The Numbered Head Together (NHT) Learning Model on Students' Learning Outcomes in The Subject of Science In Grade IV - Purba, Suryaningsih; Napitupulu, Rio Parsaoran; Sianturi, Canni Loren (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
This study aims to determine the effect of the application of the Numbered Head Together (NHT) learning model on student learning outcomes in the subject of science in grade IV of elementary school. The study used an experimental method with the type of Pre-Experimental Design, through the design of One Group Pretest-Posttest Design. The subjects of the study were all fourth-grade students of SD Negeri 098166 Perumnas Batu VI, totaling 28 people. Data were collected through observation and tests. The results showed an average pretest score of 48.86 and a posttest of 79.29. Thus, it can be concluded that the NHT learning model has an effect on student learning outcomes in the subject of science in grade IV of SD Negeri 098166 Perumnas Batu VI.